1989
DOI: 10.1016/s0039-6109(16)44788-2
|View full text |Cite
|
Sign up to set email alerts
|

Experience with Resection of Primary Hepatic Malignancy

Abstract: Although hepatocellular carcinoma is one of the most common malignancies worldwide, primary hepatic malignancy (including hepatocellular carcinoma) is a relatively uncommon neoplasm in the United States and other Western countries. Nevertheless, the authors had treated 106 patients with primary hepatic malignancy by various kinds of hepatic resection by the end of 1987. The experience is summarized here with emphasis on operative mortality, some aspects of surgical technique, and long-term follow-up. Portions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

1991
1991
2003
2003

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…Twenty patients were initially evaluated elsewhere, felt to be unresectable, and were then referred for OLT. Our transplant team, which has one of the world's largest experiences with partial hepatic resection, 15 performed partial hepatectomies whenever possible. However, because overall resectability rates for primary liver malignancies rarely exceed 30% to 40%, total hepatectomy and liver replacement is a logical alternative to achieve complete resection.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty patients were initially evaluated elsewhere, felt to be unresectable, and were then referred for OLT. Our transplant team, which has one of the world's largest experiences with partial hepatic resection, 15 performed partial hepatectomies whenever possible. However, because overall resectability rates for primary liver malignancies rarely exceed 30% to 40%, total hepatectomy and liver replacement is a logical alternative to achieve complete resection.…”
Section: Discussionmentioning
confidence: 99%
“…Rezeksiyon yapılamayanlarda transplantasyonla başarılı sonuçlar alınır. HCC a göre prognozları çok daha iyidir (3,4,5,(8)(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
Section: B-radyoterapiunclassified
“…Most reports demonstrated that right trisectionectomy was effective in extensive hepatic malignancy, based on some individuals with long-term survival [19,20] . But the risk (morbidity and mortality) of liver resection remains high according to some authors [20,22,23] , especially for primary liver cancer with cirrhosis. It is related to the fact that most primary liver cancer patients have a history of hepatitis and suffer a higher incidence of hepatic failure after major resection.…”
Section: Introductionmentioning
confidence: 99%